Efficacy, Safety, and Ergonomics of the EMS Swiss Lithoclast® Trilogy in Percutaneous Nephrolithotomy: A Review - Ishfaq, Muhammad; Floyd, MS; Gopi, Praveen; Samsudin, A; Hughes, Kaylie; McCabe, John (British Journal of Healthcare and Medical Research, 2024)
Purpose: The Swiss Lithoclast Trilogy® is a novel percutaneous nephrolithotomy (PCNL) technology used for kidney stone fragmentation. It has a trifecta effect, including mechanical fragmentation, ultrasound lithotripsy, and suction to remove stone fragments. Some comparative studies have reported a higher stone-free rate, increased safety and lower operative time, yet robust evidence remains inconclusive. We reviewed studies investigating clinical safety, efficacy, and ergonomics of PCNL for treating renal stones. Methods: We reviewed 11 studies investigating Swiss Lithoclast® Trilogy for PCNL from 2017 until September 2024. eywords were used to search PubMed, Google Scholar, Scopus and Web of Science databases for relevant studies. After applying eligibility criteria and excluding animal and laboratory studies, 11 studies were included in this systematic review. Data was extracted for efficacy, safety, and ergonomics and analyzed to synthesize the results. Results: Out of 11, 2 were retrospective cohorts and 09 were prospective studies. The Swiss Lithoclast® Trilogy exhibited higher efficacy in stone fragmentation and clearance than traditional techniques. For mini PCNL, the stone fragmentation rate was reported up to 15.75 ± 20.81 mm3/sec. For supine PCNL, the stone fragmentation rate was 20.33 +/- 27.83mm3/sec. Lastly, Swiss Lithoclast® Trilogy was associated with high ergonomic satisfaction, and no significant complications. Conclusions: EMS Swiss Lithoclast Trilogy® for PCNL exhibits efficacy and safety with variable ergonomics. However, limited data are available and further prospective and randomized trials comparing EMS Swiss Lithoclast® Trilogy with equivalent technologies for PCNL are warranted to determine its role relating to the stone type and procedure.